2017
DOI: 10.1590/0100-69912017005010
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment methods as predictors of postoperative mortality in gastric cancer patients submitted to gastrectomy

Abstract: Objectives: to determine the nutritional evaluation method that best predicts mortality in 90 days of patients submitted to gastrectomy for gastric cancer. Methods: we conducted a prospective study with 44 patients with gastric cancer, stages II to IIIa, of whom nine were submitted to partial gastrectomy, 34 to total gastrectomy, and one to esophago-gastrectomy. All patients were nutritionally evaluated through the same protocol, up to 72h after hospital admission. The parameters used were Patient-Generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
1
1
1
Order By: Relevance
“…Moreover, our study suggested that EN might improve the long-term prognosis of PMP patients, as the univariate and multivariate analyses showed that EN was an independent protective factor both for hospital stay time and complications. These findings were consistent with previous studies in that favorable nutritional status brought by EN was a positive predictor for postoperative mortality and prognosis in cancer patients (30,31). The improvement of nutritional status by EN also shortened the hospital stay time in this study, which saves on hospitalization costs and is beneficial to the physical and mental health of PMP patients.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our study suggested that EN might improve the long-term prognosis of PMP patients, as the univariate and multivariate analyses showed that EN was an independent protective factor both for hospital stay time and complications. These findings were consistent with previous studies in that favorable nutritional status brought by EN was a positive predictor for postoperative mortality and prognosis in cancer patients (30,31). The improvement of nutritional status by EN also shortened the hospital stay time in this study, which saves on hospitalization costs and is beneficial to the physical and mental health of PMP patients.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, although the study by Poziomyck et al 18 considers the ASA-PS score a reliable parameter in predicting mortality after 30 days of the procedure, considering gastrectomies, in the present article, no statistical match was found between this scale and the occurrence of postoperative complications. In contrast to the variables found in their study, where it was not possible to associate hypoalbuminemia with mortality 18 , our study showed an increased risk of complications in patients with serum albumin levels less than 3.5 g/dL, proving to be a risk factor for more severe complications (Clavien-Dindo greater than 3).…”
Section: Discussioncontrasting
confidence: 64%
“…We evaluated the endoscopic changes of the residual stomach according to the RGB (residue, gastritis, and bile) grading system [ 9 ]. Furthermore, we used the Visick grading method to assess the postoperative subjective feelings and postoperative nutritional status of the patients in the 2 groups [ 10 ]. All patients were reexamined 1 year after the operation.…”
Section: Methodsmentioning
confidence: 99%